Case Study on BIM and Value Engineering Integration for Construction Cost Control - Xiaojuan Li; Chen Wang; Ali Alashwal (Advances in Civil Engineering)
Construction projects consume a considerable amount of resources and funding. Cost control is an essential process to attain project success and enhance its value. Many studies have been dedicated to studying how value engineering (VE) can be used to control construction costs. However, limited studies can be found on the integration of building information modelling (BIM) and VE for better cost control and optimization. The main purpose of this study is to determine how BIM can be integrated with VE and illustrate the benefits of this integration. The study proposed a framework based on the analytic hierarchy process (AHP) and the entropy method to calculate the weight and coefficient. A case study method of a high-rise building project in China was used to validate the framework and demonstrate how BIM can be integrated with VE. The data were collected through document analysis, interviews, and a questionnaire survey targeted on project participants. The findings show that the integration of BIM in VE facilitates design modification and information extraction such as cost data. Using this approach showed a saving of 10% in project cost and duration. Besides, the overall quality and performance of the project have been enhanced. The findings show the significance of integrating BIM and VE to enhance building project functionality and performance before, during, and after the construction stage. This study contributes to providing empirical evidence of the advantages of this integrated approach including a better understanding of project components and requirements, easy access to project data, comprehensive weight and function analysis, easy validation of recommended solutions, and ability to virtually evaluate design changes and construction site planning.